ANALYSIS OF THE EXISTENCE OF DIGITAL ONLINE JOURNALISTS IN THE ERA GLOBALIZATION IN REVIEW OF JOURNALISTIC CODE OF ETHICS - Vicia Dwi Prakarti DB; Aryoni Ananta (Institut Seni Indonesia Padangpanjang, 2022)
Journalism is a major milestone in news outlets. Information from all corners of the world is broadcast and received both conventionally and digitally. Walking the path in the current era of globalization, all information comes to us through online gadgets and smartphones. Global developments permeate every aspect of people's lives in the digital era in obtaining information. Various information that is spread is not imaginary, it is often used as a guide in life. To disseminate information to the audience, even digital journalists who are called online journalists must not be separated from thejournalistic ethics that an online journalist must have. This paper discusses the existence of online journalists in the midst of society in the era of globalization which is mushrooming so that their existence is considered to have sufficient advantages and disadvantages. do not make fake news to increase speed in publishing news